El monasterio de San Isidoro de León y los papas de Aviñón - Domínguez Sánchez, Santiago (Estudios humanísticos. Geografía, historia y arte, 1995)
The following article studies the frequent relationship and the correspondence between the important monastery of Saint Isidoro de León, in the north of Spain, and all the Popes of Avignon, France, in the period between the beginning of the 14th century and the beginning of the 15th century.